LGBT activism and the making of Europe: A rainbow Europe - Ayoub, Phillip; Paternotte, David (Gender and politics series, 2014)
Europe has long been regarded as a unique place for the promotion and furthering of LGBT rights. This important and compelling study investigates the alleged uniqueness and its ties to a relatively long history of LGBT and queer movements in the region. Contributors argue that LGBT movements were inspired by specific ideas about European democratic values and a responsibility towards human rights, and that they sought to realize these on the ground through activism, often crossing borders to foster a wider movement. In making this argument, they discuss the 'idea of Europe' as it relates to LGBT rights, the history of European LGBT movements, the role of European institutions in adopting LGBT policies, and the construction of European 'others' in this process.
Keywords: LGBTQIA2+; activisme; approches et analyses; cours; discipline; europe; histoire; histoire et politique; identités LGBTQIA2+; justice sociale; militance; mouvements de libération; mouvements lgbtia2+; premier cycle; queer; ressource en ligne; régions géographiques; sciences humaines; sex1183; thématiques

Les oubliés du Code civil du Québec - Caron, Vincent; Berthold, Gabriel-Arnaud; Deslauriers-Goulet, Charlotte; Torres-Ceyte, Jérémie; LeBel, Louis (Les Éditions Thémis, 2014)
À l’occasion du vingtième anniversaire de l’entrée en vigueur du Code civil du Québec – événement symbolique d’importance – , il est apparu opportun d’amorcer une réflexion sur « les oubliés du Code civil », c’est-à-dire des notions qui évoluent en marge de l’œuvre codificatrice. Cet ouvrage a pour objet de faire la lumière sur certaines de ces notions dans une perspective dynamique. Ainsi, autour des principales divisions du Code civil – le droit des personnes, le droit de la famille, le droit des biens et le droit des obligations -, les auteurs offrent leurs réflexions et nourrissent un débat fertile et salutaire sur l’évolution du droit civil au Québec. Préface de Louis LeBel, juge à la Cour suprême du Canada de 2000 à 2014.
Keywords: LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; droit; histoire et politique; inégalités; justice sociale; premier cycle; québec; régions géographiques; science politique et droit; soc2014; systèmes d'oppressions; thématiques